The Morphological Change in Sunflower Plant under Hardening Conditions to Drought Tolerance. II. Leaf Number and Leaf Area - Baghdad Science Journal (مجلة بغداد للعلوم, 2009)
The study was conducted during the spring season of 2000 and2001. The objective was to study the changes in leaves number of sunflower plants and its leaf area during growth stages under hardening conditions to drought tolerance. Agricultural practices were made according to recommendations.Asplit-split plots design was used with three replications.The main plots included irrigation treatments:irrigation to100%(full irrigation),75and50%of available water.The sub plots were the cultivars Euroflor and Flame.The sub-sub plots represented four seed soaking treatments:Control(unsoaking), soaking in water ,Paclobutrazol solution(250ppm),and Pix solution(500ppm). The soaking continued for 24 hours then seeds were dried at room temperature until they regained their original weight. Amount of water for each irrigation were calculated to satisfy water depletion in soil using a neutron moisture meter. Results indicated that stress 800Kp reduced leaves number after 72 days from Planting by 5.29% compared with full irrigation as a mean of seasons.Increased stress to 600 and 800 Kp caused decreasing in leaf area at physiological maturation by 36.10 and 44.32% than full irrigation as a mean of seasons. Flame was superior over Euroflor after 58 days from planting in leaves number by 12.30 % in the season of 2001, while Euroflor was superior by 4.87% after58 days from planting in the season of 2000 ,and in leaf area by 58.25% after 44 days from planting in the season of 2001, and by 34.72% as a mean of seasons.Soaking the seeds presowing in paclobutrazol and pix solutions enhanced leaf formation , the percentage of increase reached to 5.57 and 7.49% after 86 days from planting as a mean of seasons, and leaf area by 35.9 and 36.95% respectively, compared with unsoaked as a mean of seasons. This study suggest that it could improve plant growth and kept sutable leaf area during seeds filling and drought tolerance by soaking the seeds presowing in water or plant growth regulators.